The problem of defining myth - Honko, Lauri (Scripta Instituti Donneriani Aboensis, 1972)
The first thing that one realises in trying to grasp the semantic implications of myth is that myth can cover an extremely wide field. The way in which the term myth is commonly used reveals, too, that the word is loaded with emotional overtones. These overtones creep not only into common parlance but also, somewhat surprisingly, into scientific usage. That myth does, in fact, carry emotional overtones in this way is perhaps most easily seen if we think of terms such as prayer, liturgy, ritual drama, spell: they are all used for different religious genres but would seem to be more neutral than myth. It appears to be difficult for many scholars to discuss myth simply as a form of religious communication, as one genre among other genres. If one differentiates between four levels, namely, form, content, function and context, it is much easier to encounter the varied uses which the concept has acquired in scientific literature. By this it is possible to delimit and yet be flexible at the same time. There is no need to welcome with open arms just any traditions into the fold of myth research: but nor is it necessary to exclude, for example, studies of myth where the context criterion, i.e. a context of ritual, is not fulfilled. The degree of flexibility that can be achieved is dependent on the approach that the scholar has chosen.